Sustainable Hybrid Design to Ensure Efficiency and Air Quality of Solar Air Conditioning - Alquraish, Mohamed; Abuhasel, Khaled (Engineering, Technology & Applied Science Research, 2023)
This research work aims to investigate and subsequently optimize the operating parameters that affect thermal comfort and indoor air quality in the school environment. The proposed design uses a coupling between solar ventilation and the absorption chiller-air conditioning. The heating tower of an adsorption chiller connected to an air conditioning system can be driven by the waste heat from a solar ventilation (exhausted hot air) system thank to this linkage. In order to simulate variables like the velocity magnitude distribution in the air-conditioned room, mathematical modeling is numerically executed. Air temperature evolution along the height of the conditioned room in the mid-length and the air velocity evolution along the length of the conditioned room in the mid-height are studied. According to the numerical simulation results, the inlet air temperature soars as the inlet air velocity rises. Inlet air velocities of 0.05m/s, 0.5m/s, and 1m/s are correlated with inlet air temperatures of 20.7°C, 21.2°C, and 21.3°C, respectively. We conclude that an inlet air velocity in the order of 1m/s (in relation to a maximized air change rate) is in agreement with the general ASHRAE standards for indoor air quality in the case of the school environment, coupled with the essential need to limit as much as possible the spread of viruses.